SELF-CONCEPT OF YOUNG PEOPLE WHO SPEND TIME ON STREETS - LAURECKIS, Kasparas; PETRUŽYTĖ, Donata (Socialinė teorija, empirija, politika ir praktika, 2016)
The aim of this paper is to reveal the self-concept of young people who spend their time in the streets. It is based on results of qualitative research (6 interviews with young people). The research revealed that these young people face various difficulties that have a direct negative impact on their self-worth. Young people often see themselves as “inappropriate”, “bad” or being in exclusion. Due to various childhood difficulties, problems in the family or among peers they often feel lonely, plagued by depressive thoughts. Most of them feel a general dissatisfaction with life. They speak about lack of meaning of life as a cause of their risky behaviour. However, they know their strengths.
Keywords: self-concept; youth; outreach youth work; detached youth work; social street work